(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The aim of the present study was Smokingand Tobacco a number of studies have found that smoking either alone or incombination with other factors may be an important predisposing factor for oralcandidiasis, although this relationship or its pathogenic influence on oralCandida is far from being resolved. While some studies have suggested thatsmoking does not affect Candida carriage significantly, other have reportedthat smoking significantly increases its’ prevalence. Cigarette smoking seemsto have a contributing effect especially on the incidence of pseudomembranouscandidiasis in immunocompromised individuals.